Perfusion CT detects alterations in local cerebral flow of glioma related to IDH, MGMT and TERT status - Ke Wang (BMC, 2021)
Abstract Background The aim of this study was to investigate the relationship between tumor biology and values of cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT), time to peak (TTP), permeability surface (PS) of tumor in patients with glioma. Methods Forty-six patients with glioma were involved in the study. Histopathologic and molecular pathology diagnoses were obtained by tumor resection, and all patients accepted perfusion computed tomography (PCT) before operation. Regions of interests were placed manually at tumor and contralateral normal-appearing thalamus. The parameters of tumor were divided by those of contralateral normal-appearing thalamus to normalize at tumor (relative [r] CBV, rCBF, rMTT, rTTP, rPS). The relationships of the parameters, world health organization (WHO) grade, molecular pathological findings were analysed. Results The rCBV, rMTT and rPS of patients are positively related to the pathological classification (P < 0.05). The values of rCBV and rPS in IDH mutated patients were lower than those IDH wild-type. The values of rCBF in patients with MGMT methylation were lower than those MGMT unmethylation (P < 0.05). The MVD of TERT wild-type group was lower than TERT mutated group (P < 0.05). The values of rCBV were significant difference in the four molecular groups divided by the combined IDH/TERT classification (P < 0.05). The progression free survival (PFS) and overall survival (OS) were significant difference in the four molecular groups divided by the combined IDH/TERT classification (P < 0.05). Conclusions Our study introduces and supports the changes of glioma flow perfusion may be closely related to its biological characteristics.